Stereoselective Synthesis of Ketoses by Aldol Reaction Using Water-Compatible Prolinamide Catalysts in Aqueous Media - Miura, Daisuke; Fujimoto, Takashi; Tsutsui, Ayumi; Machinami, Tomoya (Synlett, 2013)
Prolinamido-glycosides, water-compatible organocatalysts, are capable of catalyzing the stereoselective aldol reaction in aqueous media. The aldol reaction of 2,2-dimethyl-1,3-dioxan-5-one with aldehydo sugars in the isopropylidene form gave ketoses stereoselectively. The stereochemistry of these aldol reactions has been investigated in terms of the influence of conformational effects, and the results demonstrate that the configuration of the catalysts and the conformation of substrates are a determining factor in the stereochemical outcome of the reaction. Each of d-psicose and d-tagatose was selectively obtained from 2,3-O-isopropylidene-d-glyceraldehyde. Likewise, d-glycero-d-glucooctulose, whose structure was established by X-ray crystallography, was obtained from 2,3:4,5-di-O-isopropylidene-aldehydo-d-arabinose.
Keywords: carbohydrates; aldol reaction; stereoselective synthesis; diastereoselectivity; catalysis